Efficacy and Safety of Endoscopic Self-Expanding Metallic Stent for Esophageal Malignancy: A Two-Institute Experience - Balekuduru, Avinash Bhat; Sahu, Manoj Kumar; Sreenivasa, Kirti Koushik Agrahara; Gururajachar, Janaki Manur; Reddyvari, Kiran; Subbaraj, Satyaprakash Bonthala (Journal of Digestive Endoscopy, 2019)
Background: Self-expandable metallic stents (SEMS) placement is the procedure of choice for palliation of dysphagia in inoperable esophageal malignancies.Aim To evaluate the safety of placement of SEMS in esophageal cancer at two institutes using only endoscopic control without fluoroscopy and to determine efficacy of SEMS in palliation of dysphagia after deployment.Methods: Participants who underwent endoscopy and esophageal SEMS placement at two centers for inoperable esophageal malignancy between 2014 and 2017 were included retrospectively. The indication for the procedure and clinical outcome measures like adverse events and improvement in dysphagia score were recorded on uniform structured data forms.Results: Eighty-three esophageal SEMS placement was performed in 78 patients (mean age 64 ± 10.1 years; 59 men). The indication of SEMS placement was stricture in 72 (92.3%) and in 6 cases SEMS was placed for closure of trachea–esophageal fistula. All the patients in dysphagia score of 3 have improved to lower dysphagia scores post stent deployment. Postprocedure retrosternal pain, respiratory distress, and aspiration pneumonia in 58, 9, and 2 patients, respectively. Five patients required repeat stenting due to tumor ingrowth/granulation tissue during follow-up. The median survival of patients who received SEMS was significantly different from controls who did not receive SEMS (141 [41–360] days versus 98 [30–165 days]; p = 0.01). In 2 cases stent repositioning was done due to distal migration at the time of placement. There was no SEMS migration or stent related complications at follow-up.Conclusions: SEMS can be placed effectively under endoscopic control without fluoroscopic control in palliation of esophageal malignancy. Early SEMS deployment for palliating dysphagia may lead to survival advantage.
Keywords: controlled radial expansile dilation; esophageal malignancy; self-expanding metallic stent